THE IMPORTANCE OF CREATING COURSES BASED ON PEDAGOGICAL DESIGN IN THE CONTEXT OF DISTANCE LEARNING - Issabaeva, Д.Н; Kurmangalieva, Н.А (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article discusses the importance of creating training courses based on pedagogical design in the context of distance learning. The goal of pedagogical design is defined as an integrated approach to creating an educational environment and developing an educational process with the aim of flexible change and adaptation of a unified system based on educational data, methods of communication with students, educational material that meets the needs of students. When developing distance learning courses, it is necessary to design the following stages of pedagogical design: Analysis of the target group; Description of educational goals as learning outcomes (Rubricator), Determination of the content, complexity and consistency of educational material, Development of educational content, Teaching students, preparing cases; Selection of diagnostic and evaluation systems (preparation of control and measuring materials), Choice of methods of interaction and participation of students (individual, group work, etc.), Resource planning (technical, digital). Based on a common online course design model, it is suggested to plan distance-learning courses based on pedagogical design.